2021
DOI: 10.3389/fvets.2021.649758
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Expression of Selected Factors at Different Sites of the Bovine Endometrium Associated With Uterine Health

Abstract: Recent studies have elucidated the role of several pro-inflammatory factors as mediators of inflammatory processes in the bovine endometrium. Only few studies, however, have analyzed samples collected from different regions of the uterus of the same animal. In this study, we tested the hypothesis that on a molecular level, clinical endometritis is characterized by inflammatory responses spread over the entire endometrium. Furthermore, we assume that subclinical endometritis is described by an inflammation of l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, C3 , C2 , LTF , PF4 , and TRAPPC13 had unique mRNA expression patterns in the blood and endometrial tissue of dairy cows with subclinical endometritis [ 49 ]. In contrast to control cows, cows with clinical and subclinical endometritis displayed a significant change in the mRNA expression of uterus-associated proinflammatory markers, according to Pothmann et al [ 50 ]. In the endometrium of repeat breeding cows with and without subclinical endometritis, there were significantly more transcript levels of tumor necrosis factor and inducible nitric oxide synthase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, C3 , C2 , LTF , PF4 , and TRAPPC13 had unique mRNA expression patterns in the blood and endometrial tissue of dairy cows with subclinical endometritis [ 49 ]. In contrast to control cows, cows with clinical and subclinical endometritis displayed a significant change in the mRNA expression of uterus-associated proinflammatory markers, according to Pothmann et al [ 50 ]. In the endometrium of repeat breeding cows with and without subclinical endometritis, there were significantly more transcript levels of tumor necrosis factor and inducible nitric oxide synthase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distinctions between UB and UH have not been fully delineated 44 . However, a study conducted by Pothmann, et al 44 demonstrated a significant mRNA expression of Interleukin 1 beta, Interleukin 1 alpha, and C-X-C motif chemokine ligand in UH.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctions between UB and UH have not been fully delineated 44 . However, a study conducted by Pothmann, et al 44 demonstrated a significant mRNA expression of Interleukin 1 beta, Interleukin 1 alpha, and C-X-C motif chemokine ligand in UH. Additionally, UH creates an environment that is less favorable for bacterial growth and colonization due to the presence of antimicrobial substances 45 and ciliary movement 46 , which aids in the elimination of potential pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…When bacterial infection causes severe or prolonged endometrial inflammation, it develops uterine disorders [ 53 ]. In addition, proinflammatory substances, such as prostaglandins and cytokines, such as interleukin 1A (IL1A), interleukin 1B (IL1B), and C-X-C motif chemokine ligand 8 (CXCL8), were elevated in cows with preclinical and clinical endometritis [ 54 ].…”
Section: Implication Of Lactic Acid Bacteria On Animal Fertility-rela...mentioning
confidence: 99%